The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.0307-7772.2004.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein (HSP70) in oral lichen planus and non-dysplastic oral leucoplakia

Abstract: The purpose of this study was to investigate the expression of heat shock protein (HSP70) in oral non-dysplastic leucoplakia and in relation to the clinical and pathological features of oral lichen planus. The expression of HSP70 was assessed in the epithelial compartment of normal mucosa (n = 5), oral lichen planus (n = 28) and benign leucoplakia (n = 11) using an immunohistochemical method. The immunostaining intensity distribution (IID) index was used to quantify the positivity of the staining. There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
(31 reference statements)
2
17
0
1
Order By: Relevance
“…5,14,21,27 Occasionally, both moderate cytoplasmic staining and nuclear staining are present in normal oropharyngeal mucosa adjacent to head and neck squamous cell carcinoma. 28 Our research group has recently reported the absence of nuclear staining for HSP70 in normal mucosa and a weak cytoplasmic expression of this protein in normal epithelium, with an IID index score of ( X 6 SD = 4:0 6 3:39), 29 which was significantly lower than the observed for nondysplastic OLs in this study ( X i À X j = 12.91; 95% CI = 7.81-18.00; P = 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…5,14,21,27 Occasionally, both moderate cytoplasmic staining and nuclear staining are present in normal oropharyngeal mucosa adjacent to head and neck squamous cell carcinoma. 28 Our research group has recently reported the absence of nuclear staining for HSP70 in normal mucosa and a weak cytoplasmic expression of this protein in normal epithelium, with an IID index score of ( X 6 SD = 4:0 6 3:39), 29 which was significantly lower than the observed for nondysplastic OLs in this study ( X i À X j = 12.91; 95% CI = 7.81-18.00; P = 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Bramanti et al and Seoane et al , who concluded in their study that the expression of HSPs is seen in normal oral mucosa. [1112] Literature reveals that the expression of HSPs was noted to be altered in OLP. [13]…”
Section: Discussionmentioning
confidence: 99%
“…[11] Seaone concluded that differences in HSP70 expression among OLP and normal mucosa were slight and inconclusive. [12]…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been observed with hsp60 (Bramanti et al , 1995; Chaiyarit et al , 1999). In relation to hsp70 , there seems to be different results; it may relate more to oral leukoplakia than to OLP (Seoane et al , 2004). Regarding Hsp90 , some controversy exists, as in one experiment, it did not demonstrate any correlation with OLP (Bramanti et al , 1995), while in other experiment, it appreciated a reduction in the expression of hsp90 compared to control mucosa (Chaiyarit et al , 2009).…”
Section: Discussionmentioning
confidence: 99%